Acute Cognitive and Physical Rest May Not Improve Concussion Recovery Time - Buckley, Thomas A. (J Head Trauma Rehabil, 2016)
OBJECTIVE: Evaluate the effectiveness of an acute period of cognitive and physical rest on concussion. PARTICIPANTS: 50 consecutive patients with diagnosed concussions. DESIGN: Participants were assessed before (N=25) and after (N=25) a policy change which incorporated cognitive and physical rest. The Rest group patients were withheld from activities, including classes, for the remainder of the injury day and the following day whereas the No-Rest group patients were not provided any post-injury accommodations. MAIN MEASURES: Patients were assessed on a graded symptom checklist, Balance Error Scoring System, Standard Assessment of Concussion, and computerized neuropsychological tests. The number of days until each test achieved baseline values was compared between groups with independent sample t-test. RESULTS: The No-Rest group achieved asymptomatic status sooner than the Rest group (5.2±2.9 days and 3.9±1.9 days respectively, P=0.047). There were no differences between groups for time to baseline values on the balance error scoring system, standard assessment of concussion, computerized neuropsychological tests, or time to clinical recovery. CONCLUSION: A prescribed day of cognitive and physical rest was not effective in reducing post-concussion recovery time. These results agree with a previous study and suggest that light activity post-concussion may not be deleterious to the concussion recovery process.